2012
DOI: 10.1007/s00339-012-6885-7
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of CaCu3Ti4O12–silicone resin composites

Abstract: CaCu 3 Ti 4 O 12 (CCTO)-silicone resin composites with various CCTO volume fractions were prepared. Relatively high dielectric constant (ε = 119) and low loss (tan δ = 0.35) of the composites with CCTO volume fraction of 0.9 were observed. Two theoretical models were employed to predict the dielectric constant of these composites; the dielectric constant obtained via the Maxwell-Garnett model was in close agreement with the experimental data. The dielectric constant of CCTO-silicone resin composites showed a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…2 Previous studies have shown that ceramic-polymer composites possess high dielectric permittivity. [3][4][5][6][7] However, the volume fraction of ordinary ceramic llers in ceramic-polymer composites is large, and this results in large loss, poor mechanical exibility and poor insulation properties. When the volume fraction of ordinary ceramic llers is less than 10 vol%, the dielectric permittivity of the ceramicpolymer composites barely increases compared with that of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous studies have shown that ceramic-polymer composites possess high dielectric permittivity. [3][4][5][6][7] However, the volume fraction of ordinary ceramic llers in ceramic-polymer composites is large, and this results in large loss, poor mechanical exibility and poor insulation properties. When the volume fraction of ordinary ceramic llers is less than 10 vol%, the dielectric permittivity of the ceramicpolymer composites barely increases compared with that of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…CCTO/PS, CCTO/silicone resin, CCTO/PES, and CCTO/PDMS have also been prepared by other researchers. 5,6,9,18 Although high dielectric permittivity can be obtained using ceramic grain llers, the volume fraction of llers usually exceeds 20 vol% and the loss is large (over 0.2 in general), which leads to a decrease in the mechanical exibility of the composites. Therefore, a low doping concentration, a relatively high dielectric permittivity and a low loss of the composites are our targets.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric particles with a high dielectric constant, such as oxides with perovskite and related structures, are widely used as llers in ceramic-polymer composites. [1][2][3][4][5][6][7][8][9] Abbas et al prepared BaTiO 3 (BTO) lled polyaniline microwave absorbing composites, and the results showed that the highest values of the real part of the complex permittivity (3 0 ) that could be obtained were 7.3 at 8.2 GHz, and 6.9 at 12.4 GHz. 2 These results indicated that although BTO has a relatively high dielectric constant of over 1000, the effective dielectric constant of a composite with a high BTO concentration still remains relatively low, due to the lower dielectric constant of the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recently, CaCu 3 Ti 4 O 12 (CCTO) has become known for its high dielectric constant, and some CCTO-polymer composites have been investigated to explore the possibility of obtaining high dielectric constant composites. [6][7][8][9] Thomas et al 7 reported the dielectric properties of poly(vinylidene uoride)-CCTO composites. A room temperature dielectric constant as high as 95 at 100 Hz has been realized for the composite with 55 vol% CCTO.…”
Section: Introductionmentioning
confidence: 99%
“…These numbers represent well the various systems of titanates (TiSr, CuCaTi, and TiBa oxides) with surface modifications. [54] From Equation 9, it is obvious that if a significant actuation improvement at a given voltage is desired, then the following relation needs to hold: k e ) k Φ . In other words, the ratio of permittivities should be significantly larger than the ratio of Young's moduli multiplied by constant accounting for the spatial incorporation of filler.…”
Section: Empirical Descriptions Of Composites' Figures Of Meritmentioning
confidence: 99%